MENGEMBANGKAN KEMAMPUAN MEMBACA MELALUI GRAPHIC ORGANIZERS - Pudiyono Pudiyono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
The goal of the research was to develop a comprehension based reading model through graphic organizers. The subjects of the research were fourth semester students of English Education Department of Muhammadiyah University of Purwokerto. The test was aimed at getting clear descriptions on the students’ reading comprehension. The result of data analysis showed that most reading classes (>80) still applied teacher centered approach, even though the teacher did not apply reading classes in rhetoric way anymore. From the observation, it was clear that the exercises designed were not exactly based on contextual understanding. Exercises on difficult words were still much focused on a lexically based work out. Besides that, the reading instructions did not really focus on the whole text content comprehension as the exercises were much oriented on partial comprehension questions, for example just by asking and discussing the main idea of paragraphs. To make the instructions even worse, the teacher did not have a good mind set in applying cooperative nor collaborative learning activities. Some good points the teacher had were on no reading aloud and translation activities. The questionnaire result showed that the student’s interest was not as high as we expected. The test result on their comprehension in their pre-test only showed 47. 50. To solve this problem, the reading classes applied graphic organizers in cooperative and collaborative learning activities. After treatments, the result of their comprehension developed well, from pre-test score 47. 50 to 56. 13 in their post test. This means that their comprehension achievement improved 18.17 %. After having well-rehearsed in reading on graphic organizers, the students did not only get better comprehension results but they also had better-than-desired involvement in classroom activities. Students also commented that they had better understanding and better psychological feeling in reading English texts. Key words: reading instructions, interactive activities, comprehension skills, graphic organizers, cooperative and collaborative learning